(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article analyzes the stage interpretations of the play "Usmon Nosir" as performed at the Namangan Regional Theater and the Uzbek State Musical Academic Theater named after Muqumiy. The complex emotional experiences, internal struggles, and dreams of the poet are conveyed through contemporary theatrical tools such as acting, stage design, and musical composition. The director’s approach, symbolic stage imagery, and the aesthetic impact of theater on audience perception are examined.